High-Speed Plasmid Isolation Using 96-Well, Size-Exclusion Filter Plates. (March 2002) - Harris, D.; Engelstein, M.; Parry, R.; Smith, J.; Mabuchi, M.; Leonard, J.
The accelerating pace of genomics analysis has necessitated the abbreviation of DNA sample preparation protocols. We have developed a size-exclusion-based system for the rapid isolation of plasmid DNA in a 96-well microplate format. This high-speed protocol employs a modified alkaline lysis method for the preparation of the bacterial lysate, followed by three short vacuum filtration steps. Unlike traditional bind/wash/elute methods, there is no need to use chaotropic salts or ethanol. The samples are recovered from the top side of the MultiScreen96 ® PLASMID plates. Starting with bacterial cell pellets, the entire procedure for purifying the plasmid DNA can be performed in 30 min with a multichannel pipettor. The high yields, reproducibility, and quality of the plasmids make this system a good choice for any cloning or DNA sequencing operation.